Buckling Analysis of Anti-Symmetric Cross-Ply Laminated Composite Plates under Different Boundary Conditions - Adim, B.; Hassaine Daouadje, T.; Abbes, B. (Прикладная механика, 2016)
The buckling analysis of anti-symmetric cross-ply laminated composite plates under different boundary conditions is examined by using a refined higher order exponential shear deformation theory. Проведено аналіз втрати стійкості антисиметрично перехресно армованої шаруватої композитної пластинки при різних граничних умовах в рамках уточненої теорії вищого порядку, що враховує зсувні деформації.